Caracterização molecular do gene TPO em crianças Portuguesas com hipotiroidismo congénito causado por disormonogénese - Nogueira, Célia (2012)
Congenital hypothyroidism (CH) affects about 1:4000 infants and is considered one of the main causes of preventable mental retardation in children. Universal screening of CH performed through the Portuguese National Neonatal Screening Programme, implemented in Portugal in 1985, has resulted in normal development of attained children. Birth defects of the thyroid can be divided into several groups that represent either changes in the development of the gland or the consequences observed in the deficient synthesis of thyroid hormones. The defects of hormone synthesis caused by dyshor - monogenesis occur in only 10% to 15% of cases of HC. Defects in the thyroid peroxidase (TPO) gene are reported to be one of the most frequent causes of CH due to dyshormonogenesis. The aim is to review the mutational spectrum of the TPO gene in the portuguese population through the molecular investigation of 69 patients with permanent CH due to dys - hormonogenesis. To complement previous results, published in 2005, this work describes the molecular characterization of a further fourteen children with CH and the methodology applied. Extensive in-silico analysis was carried out for the newly identified sequence changes as well as the formerly published putative splicing variant. The sequence variations identified in the TPO gene comprise ten distinct mutations and 29 polymorphisms, enabling the determination of the molecular etiology of CH in fifteen patients. In conclusion, it was possible to obtain a differential diagnosis in twelve fami - lies with CH, using a non-invasive procedure and without interruption of medication. Identification of these and other mutations in the TPO gene can therefore contribute considerably towards diagnosis, a precise genetic counselling, adequate monitoring in future pregnancies as well as putative personalized therapies.